The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s00726-021-02964-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cationic surfactants with DPPC membranes: effect of a novel Nα-benzoylated arginine-based compound

Abstract: Cationic amino acid-based surfactants are known to interact with the lipid bilayer of microorganism resulting in cell death through a disruption of the membrane topology. To elucidate the interaction of a cationic surfactant synthesized in our lab, investigations involving N α -benzoyl-arginine decyl amide (Bz-Arg-NHC 10 ), and model membranes composed by 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) were done. Bz-Arg-NHC 10 was able to penetrate into DPPC monolayers up to a critical pressure of 59.6 mN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Studies involving the interaction of Bz-Arg-NHC 10 with dipalmitoylphosphatidylcholine (DPPC) model membranes had been carried out previously in order to explain the enhanced antibacterial activity of this compound (Hermet et al 2021). Those experiments enabled the calculation of the MIP for DPPC monolayers at the same surfactant concentration used in the present work (30 µM).…”
Section: Monolayer-penetration Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving the interaction of Bz-Arg-NHC 10 with dipalmitoylphosphatidylcholine (DPPC) model membranes had been carried out previously in order to explain the enhanced antibacterial activity of this compound (Hermet et al 2021). Those experiments enabled the calculation of the MIP for DPPC monolayers at the same surfactant concentration used in the present work (30 µM).…”
Section: Monolayer-penetration Experimentsmentioning
confidence: 99%
“…The results reported by those authors also suggested an antagonistic effect of the amino and guanidinium groups on the antifungal behavior of the arginine-based tensioactives studied: therefore, the presence of the amino group may partially neutralize the anticandida action of the guanidinium group(Pérez et al 2021). This effect seemed to be compensated in the example of our compounds, since the benzoyl group attached to the amino-acid moiety increases the molecule's hydrophobicity(Hermet et al 2021). This greater hydrophobicity becomes relevant in view of the previously discussed mode of action of cationic surfactants: hydrophobicity enhances the molecule's a nity for the membrane phase, thus improving ability of the former to insert itself within the lipidic regions(Fonseca et al 2010).…”
mentioning
confidence: 92%